ANALISA YURIDIS KEWENANGAN PETUGAS PEMADAM KEBAKARAN DALAM TINDAKAN DARURAT MEDIS BANTUAN HIDUP DASAR DI LIHAT DARI ASPEK PERATURAN PERUNDANG-UNDANGAN - Taupik Alpiyandi (2021)
Emergency medical services in Indonesia are still constrained by implementation in the field with unanswered all of the community's expectations, due to the ineffectiveness of the regional apparatus or institutions that are their duties and functions, from the problems that exist can take the question of how Fire Officers can become part of the Health Workforce and whether Fire Officers can carry out medical emergency measures, especially basic life support, which is then the benefit of this article if further review will be able to provide input to parties in determining the extent to which the position, role and authority of Fire Officers in medical emergency services in the field with an approach The theory of policy formulation, responsibility and legal certain, in addressing this issue the method or methodology of research using legal normative research methods with a prescriptive nature in research located at Jakarta Fire And Rescue Department, and in managing data using secondary data in the form of document studies and a combination of interview methods in order to get the maximum possible results, from the results of the discussion it turns out that some discrepancies are found in ordering existing laws and regulations that do not refer to the above rules. There is a juridical malfunction resulting in confusion over the authority of the Fire Departement in its practice and irregularity in the supervisory agency, in this case the Ministry that houses the Fire Departement, which must be rearranged all existing laws and regulations which are in charge of the Fire Departement.